L-Tryptophan Depletion Using a New Bioreactor: A Possible New Cancer Therapy - Bambauer, Rolf; Wang Yefu (British Journal of Healthcare and Medical Research, 2023)
Not all cancer therapeutic strategies known to date are not adequate for all cancer patients. Most of them are followed by a high rate of severe side effects and complications. L-Tryptophan metabolism plays a key role in organism development, as well as in the occurrence and development of tumors. By degrading certain amino acids, tumor growth can be limited while maintaining the body´s normal nutritional requirements. The L-tryptophan depletion bioreactor is described as a possible new method of cancer therapy. L-tryptophan is an essential amino acid that has been recognized as an important cancer nutrient and its removal can lead to destruction of the tumor cells. Tumor cells or normal human cells cannot synthesize L-tryptophan and therefore tumor resistance is unlikely to develop. L-tryptophan is also a constituent for different bio-molecules such as Serotonin, Melatonin, and is needed for other synthesis processes in the cell growth. L-tryptophan degrading enzymes with three iso-enzymes called tryptophan side chain oxydase (TSO) I, II, III have different molecular weights and different effectiveness. All the TSO enzymes have heme that can catalyze essentially similar reactions involving L-tryptophan as a substrate. The most effective TSO is the type TSO III. A column, which contained TSO, immobilized on silica beats as a bioreactor, was integrated in a plasmapheresis unit and tested it in different animals. In sheep and rabbits, L-tryptophan depletion in plasma was shown at 95% and 100% rates respectively by a single pass through the bioreactor. In 20 different tumor cell lines, there were different efficacies. Brest cancer and medulloblastoma showed the greatest efficacy of L-tryptophan degrading. The gene technology of TSO production from Pseudomonas is associated with formation of endotoxins. These endotoxins must be eliminated. Bioreactors with TSO III are developed to treat cancer diseases successfully, and has low side effects. A combination of L-tryptophan depletion with all available cancer therapies is possible.